Frugality: from the good life to the good society - Emrys Westacott (Field Actions Science Reports)
The concept of frugality is associated with a number of other related notions including temperance, thriftiness, conservation, and simple living. For over two thousand years, philosophers and other moral teachers have praised the life of frugal simplicity, arguing that it is both morally beneficial and a sure path to happiness. In the past, the focus has primarily been on the lifestyle of individuals, but in recent times the concept has been applied more broadly to whole communities and institutions. One reason for this shift is the emergence of a critical attitude towards consumerism, and also towards the widespread assumption (strengthened by consumerism) that continuous, endless economic growth is a rational and desirable goal to pursue. Another reason is a growing sense that the current environmental crises the world faces require frugality to be embraced not just by individuals but also by communities, organizations, and institutions, up to and including the whole of society. This environmental concern expresses itself through policies and practices that are "frugal" in the sense of conserving resources, reducing waste, recycling, reusing, and supporting local economies. Although there can be times when a supposedly frugal practice may not, considered by itself, succeed in reducing the ecological footprint of an individual or a community, it is reasonable to suppose that overall and, in the long run, the cultivation of a frugal outlook throughout society will be environmentally beneficial.